Sequencing Analysis of the N gene of Canine Distemper Virus from Infected Dogs in Baghdad City - Jbr, Aya; Jumaa, Rawaa (The Iraqi Journal of Veterinary Medicine, 2024)
The primary aim of this study was to analyze the nucleocapsid (N) gene of the Canine Distemper Virus (CDV) in infected canines within Baghdad, Iraq. A total of 50 samples, encompassing nasal swabs and fecal specimens, were obtained from canines of various ages and breeds. Utilizing a Rapid Test, nine of 50 samples tested positive for CDV. Subsequent to this, the RNA from the positively tested samples was extracted and subjected to Reverse ‎Transcription-‎Polymerase Chain Reaction (RT-PCR) for cDNA synthesis. The synthesized ‎cDNA was further amplified through conventional PCR targeting the N gene. Six of these amplified products were submitted to Macrogen, South Korea, for sequencing. Sequence analysis revealed multiple silent and missense point mutations within the N gene. Phylogenetic analysis indicated a 99% similarity of the N gene in the Iraqi strains to a known strain from the USA. Overall, this study identifies point mutations in the N gene of CDV in infected canines in Iraq and establishes that ‎the circulating strain exhibits high genetic resemblance to a USA strain. Therefore, it is imperative to formulate and implement high-efficacy vaccines and comprehensive control ‎strategies‎. This represents the first study in Iraq to focus on the N gene ‎analysis of CDV in infected dogs.